Systematic Literature Review (Slr): The Effect Of Appraisal Value On Customers' Decisions To Use Gold Pawn Services - Putri Andini Al Khoiri; Zuhrinal M Nawawi; Tuti Anggraini (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
Pawning gold is a popular alternative source of funding in Indonesia. However, a customer's decision to use gold pawning services is influenced by various factors, including the estimated value. This study's goal is to perform a Systematic Literature Review (SLR) in order to determine how the projected value affects consumers' choices when it comes to utilizing gold pawn services. The Systematic Literature Review (SLR) approach is the research methodology employed in journals published between 2020 and 2023. This research method uses SLR by searching for relevant articles from academic databases, such as Google Scholar, Scopus, and Web of Science. The selected articles must meet the inclusion criteria, namely articles that discuss the influence of the estimated value on customers' decisions in using gold pawning services. The research findings indicate that customers' decisions to use gold pawn services are significantly influenced by the assessed value. A high estimated value can boost client confidence in gold pawn services and encourage more people to use them. On the other hand, a low assessed value may make users less trusting of the service and less likely to use it.